Hydro-geochemical review of groundwater and rain waters from Al Jabal Al Akhdar, Northeast Libya - Al Faitouri, Mohamed; Salloum, Fathi; Muftah, Ahmed (Libyan Journal of Science &Technology, 2022)
Groundwater recharge and age dating using stable and carbon isotopes in northern Cyrenaica have been performed during the seventies of the last century. Twenty-eight groundwater samples (springs and wells), as well as sixty rain water samples, were collected from four hydrogeological units in Al Jabal Al Akhdar that have been analyzed in order to determine the composition of the stable isotopes (δ2H, δ18O, 14C, and 13C). Tritium is used herein to determine if there is any direct infiltration of modern water to the existed aquifers in the study area. The range of compositions for each rainwater sample is: δ2H (–28.3‰ to 0.3‰) and δ18O (-5.32‰ to 0.33‰) for Benghazi rain samples whereas δ2H (-35‰ to -22.6‰) and δ18O (-6.5‰ to -4.43‰) for Al Marj rain samples which show apparently oceanic and continental effects on the studied samples to the Global Meteoric Water Line (GMWL). The Miocene water samples have δ2H and δ18O values indicated an increasing in aridity as the deuterium excess is reduced due to evaporation effects. Given this result, the isotopic values indicate that the groundwater pumped from wells in Benghazi – Al Marj region resulted from the mixing of at least two groundwater systems. Seawater intrusion should be considered in the Ayn Zayanah-Al Coeffiah karstic system. Additionally, the δ2H/δl8O ratios show that most of the Ayn Zayanah spring discharges contain evaporated waters due to enrichment in isotopic values